Development and identification of a new Vero cell-based live attenuated influenza B vaccine by a modified classical reassortment method. (3rd August 2017) - Yang, Fan; Ma, Lei; Zhou, Jian; Wu, Yinjie; Gao, Jingxia; Song, Shaohui; Geng, Xingliang; Guo, Qi; Li, Zhuofan; Li, Weidong; Liao, Guoyang; Li, Yufeng
ABSTRACT: Background: It was to generate a new Vero and cold-adapted live attenuated influenza B vaccine with enough safety and immunogenicity. Methods: According to modified classical reassortment method, the donor strain was B/Yunnan/2/2005Vca(B), and the parental virus strain was B/Brisbane/60/2008wt. After co-infection in Vero cells, the prepared antibody serum inhibited the donor strain growth, and screening conditions inhibited the parental virus growth, which induced the growth of the new reassortant virus B/Brisbane/60/2008Vca(B) grow. Through intraperitoneal injection (i.j.) and intranasal injection (n.j.) we evaluated the safety and immunogenicity of the vaccine. Results: A high-yield of the reassortant virus was produced in Vero cells at 25°C, similar to the donor strains. After sequencing, it was found that B/Brisbane/60/2008Vca(B) Hemagglutinin (HA) and Neuraminidase (NA) gene fragments were from B/Brisbane/60/2008wt, while the other 6 gene fragments were from B/Yunnan/2/2005Vca(B). The n.j. immune pathway experiments showed no significant differences between the treatment and the PBS control group with respect to weight changes (P > 0.5). Furthermore, the new strain had a sufficient geometric mean titter (GMT) against B/Brisbane/60/2008wt. Conclusion: The new reassortant live attenuated influenza B vaccine was safe and having enough immune stimulating ability.